PELUANG DAN TANTANGAN TEKNOLOGI BLOCKCHAIN UNTUK PENCATATAN PERNIKAHAN DI INDONESIA - Ahmad Alimuddin; Muh. Al-Amin (SAMAWA, 2025)
Blockchain technology offers a revolutionary solution to enhance efficiency, security, and transparency in civil registration systems in Indonesia, particularly marriage registration. This technology enables data to be stored permanently and distributed across a secure network, reducing the risks of manipulation and data loss. This study analyzes the opportunities and challenges of implementing blockchain, including the need for regulations, infrastructure, and human resource training. By leveraging the experiences of countries like Estonia and Georgia, while considering the local context, the study provides recommendations for a phased implementation strategy. The findings indicate that blockchain adoption holds significant potential to support the modernization of public services in the digital era, despite facing notable challenges such as immature regulations and cultural resistance. A well-planned, collaborative, and sustainable strategy is essential to achieve this transformation.